A lightweight optimal design model for bolted flange joints without gaskets considering its sealing performance. (April 2018) - Ma, Benben; Zhu, Yichao; Jin, Fan; Ding, Quan; Guo, Xu
The lightweight optimal design of bolted flange joint system without gaskets is still a challenging problem, mainly owing to two issues: the relatively large number of mutually dependent geometric design parameters and the complicated role played by the contact details between members. With these two issues properly addressed, this article aims for devising a concise formulation for lightweight optimal design of bolted joint systems without gaskets. After a systematic examination of the correlations between design parameters, the total number of free design variables is reduced to three: member thickness, bolt spacing, and bolt specification, respectively. Besides, a finite element analysis that can resolve more contact details between members is conducted, and the influencing factors on the pressure distribution at the member surface are thus identified, with a criterion for the system sealing failure incorporated. Based on the findings in this work, a novel design scheme for the joint system is proposed, and good agreement between our predictions and results obtained by a full three-dimensional finite element analysis is shown. The proposed approach can be used to optimize the design parameters of bolted joint systems considering sealing performance without heavy finite element computation and can find applications in many relevant engineering fields.